Development of Animated Video Learning Media in Grade II Elementary School - Masni, Nurbaiti; Hadiyanto, Hadiyanto; Montessori , Maria; Bentri , Alwen (Journal of Educational Sciences, 2025)
Learning is still teacher-centered, there is a lack of student interest and motivation in learning, and students appear unenthusiastic when the teacher explains the learning material, so the learning process is not yet optimal. The purpose of this research is to develop animated video learning media for Pancasila Education subjects in Grade II Elementary School that are valid, practical, and effective. This type of research is R&D using the ADDIE model. The subjects of this research are students in classes II B and II C at one of the Islamic schools in Padang Panjang City. The data collection instruments used were validation sheets, teacher response questionnaires, and effectiveness tests (in the form of a weekly student worship recapitulation sheet). The data analysis techniques used are validity analysis, practicality analysis, and effectiveness analysis. The data analysis techniques used are validity analysis, practicality analysis, and effectiveness analysis. The results of the content expert validity obtained a score of 97%, media expert validity 80%, and language expert validity 93%; 2) teacher response practicality with a percentage score of 99.33% (very practical); 3) the effectiveness test showed that animated video learning media is effective in improving students' worship application results.